Modeling and simulation of pyrolysis of sisal residue in transient regime (Research, Society and Development, 2020)
This study presents a transient mathematical model capable of predicting coal production in a fast pyrolysis process from a fluidized bed reactor. The model was developed from the thermal decomposition of a sisal particle and its solution depended on data not reported in the literature. The convective coefficient of the reaction medium was found from pilot unit experimental data involving heats given and dissipated by the reaction system. The surface temperature of the particle was measured in a new bench test, in which some particles were pyrolysis transformed at a fixed reaction temperature. The surface temperature of a set of particles was measured at each reaction time, as well as their diameters and masses. The particle specific mass was measured with the aid of gas pycnometry, using the particles obtained in the surface temperature experiment. From the results of the particle specific diameters and mass, it was possible to determine their calorific capacities. The system of equations obtained was solved in MATLAB environment, obtaining surface temperature and particle mass profiles throughout the reaction. The data needed to calculate the theoretical carbon mass of a pyrolysis pilot unit was the particle diameter obtained from the model simulation and the resulting particle velocities in the reactor obtained from a force balance in a particle. The calculated particle residence time was 35 s and the calculated coal mass had a discrepancy of 6.38% compared to data collected at the pilot production unit. These results validate the properties, throughout the reaction, of the particle of the sisal residue found experimentally and by means of calculations.